DIGITALISASI SEBAGAI PEMULIHAN PEREKONOMIAN DI SEKTOR KERAJINAN DALAM MENDUKUNG KEBANGKITAN UMKM DI PROVINSI BALI - Ni Ketut Sari Adnyani; Dewa Ayu Eka Agustini (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
This article aims to examine the economic recovery of Bali Province in the MSME sector during the Covid-19 pandemic. To find out about technological developments in increasing business productivity. The article is a study of the results of the implementation of science and technology transfer service to partners. Descriptive study. Researchers use a library research approach through searching for sources in the form of books, journals, news or other relevant works to carry out in-depth studies and align them with the findings in the field. The sample of this research is UMKM in Bali Province which is engaged in weaving, wood and silver handicrafts with a total sample of 15 people, from 3 handicraft centers represented by 45 samples. The research analysis was conducted in a descriptive qualitative manner. The results showed that MSMEs needed economic recovery during the Covid-19 pandemic, one of which was an alternative to digitalization activities. The digitization of MSMEs has opportunities and challenges. The opportunity is that this activity will be easier to carry out, both in terms of production, distribution and consumption. The challenge is faced with the lack of human resources in accessing technology. The transfer of functions of digitalization technology can support technological developments in increasing business productivity.